Взаємозв’язок мислення і пам’яті у філософії Мартіна Гайдеґґера - Возняк, С. В.; Voznyak, S. V. (Східноєвропейський національний університет імені Лесі Українки, 2013)
У статті феномен пам’яті проаналізовано в контексті концепції мислення Мартіна Гайдеґґера. Пам’ять не просто психологічне явище, вона – зібраність мислення в тому, що нас зберігає й утримує в нашій істотності. Пам’ять створює, облаштовує, утворює внутрішній порядок і оберігає мислення. The article reviews the memory phenomena in the context of the conception of thinking in Martin Heidegger’s philosophy. It’s important to point out that M. Heidegger makes a distinct difference between the calculative thinking of science and common sense and the essential thinking that is treated as a co-action of the entity essence. Taking it into account Heidegger states that memory isn’t just an ordinary psychological phenomenon. It’s a concentration of thinking in the aspect that enshrines us in our essence. Memory creates and accommodates the inner order and preserves the thinking. It is the only chance for the thinking to be kept away from the face of the given to be thought over entity that is facing us. Herewith we notify linguistic and ontological relation between the thinking, the memory and the gratitude.
Interrelation of Thinking and Memory in Martin Heidegger’s Philosophy
Keywords: мислення; thinking; пам’ять; memory; буття; entity; вдячність; gratitude; екзистенціали; existentials; збереження; preservation; цілісність; wholeness